Sound foundations : - Underhill, Adrian (Macmillan, 2005)
The book gives an overview of the major facets of phonology, and can get quite detailed. For example, there are chapters on monophthongs and diphthongs, just to give you an idea. The other chapters are broader, but they maintain a good level of detail that does not overwhelm. Intonation, connected speech, stress and unstress all get a going over in the first part. The second part of the book deals with the classroom aspects, and deals with individual sounds, charts, using mime and gesture, giving models and a whole range more.